A comparative analysis of complete chloroplast genomes of seven Ocotea species (Lauraceae) confirms low sequence divergence within the Ocotea complex - Trofimov, Dimitrij; Cadar, Daniel; Schmidt-Chanasit, Jonas; Rodrigues de Moraes, Pedro Luís [UNESP]; Rohwer, Jens G. (Springer Nature, 2022)
The genus Ocotea (Lauraceae) includes about 450 species, of which about 90% are Neotropical, while the rest is from Macaronesia, Africa and Madagascar. In this study we present the first complete chloroplast genome sequences of seven Ocotea species, six Neotropical and one from Macaronesia. Genome sizes range from 152,630 (O. porosa) to 152,685 bp (O. aciphylla). All seven plastomes contain a total of 131 (114 unique) genes, among which 87 (80 unique) encode proteins. The order of genes (if present) is the same in all Lauraceae examined so far. Two hypervariable loci were found in the LSC region (psbA-trnH, ycf2), three in the SSC region (ycf1, ndhH, trnL(UAG)-ndhF). The pairwise cp genomic alignment between the taxa showed that the LSC and SSC regions are more variable compared to the IR regions. The protein coding regions comprise 25,503–25,520 codons in the Ocotea plastomes examined. The most frequent amino acids encoded in the plastomes were leucine, isoleucine, and serine. SSRs were found to be more frequent in the two dioecious Neotropical Ocotea species than in the four bisexual species and the gynodioecious species examined (87 vs. 75–84 SSRs). A preliminary phylogenetic analysis based on 69 complete plastomes of Lauraceae species shows the seven Ocotea species as sister group to Cinnamomum sensu lato. Sequence divergence among the Ocotea species appears to be much lower than among species of the most closely related, likewise species-rich genera Cinnamomum, Lindera and Litsea.